Analisis Manajemen Krisis Di Kompas Gramedia Jakarta Pusat - Fauzan Achmad Eka Pratama (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2024)
This research uses a qualitative descriptive approach, namely by describing and analyzing the problems found. Qualitative research is based on primary data and secondary data. Primary data in this research was obtained by conducting observations, interviews and documentation, while secondary data was obtained through previous research and articles related to the research. The aim of this research is to analyze and understand the crisis management practices implemented by Kompas Gramedia as a leading media company in Indonesia. And understand the effectiveness of the steps taken by Kompas Gramedia in dealing with the crisis and its impact on the company. As well as the challenges and obstacles faced by Kompas Gramedia in managing the crisis. This research provides insight into crisis management practices in the media industry, focusing on Kompas Gramedia as a case study. These findings can contribute to further understanding of how media companies can effectively confront and manage crises, as well as maintain their reputation in the eyes of the public..